Behaviour of reinforced concrete beam with metakaolin under static load / Mohammad Tamizi Selimin - Selimin, Mohammad Tamizi (2005)
The purpose of this study is to study the behavior of high strength reinforced concrete of grade 60 incorporating MK7003 by replacement at 5%, 10% and 15% to weight of cement with water cement ratio of 0.35 cured in temperature under static load. Structure beams properties that have been investigated are crack location, deflection, and modulus of elasticity due to bending of reinforced concrete respectively. Eight (8) numbers of beams with respective percentage of MK7003 are casted and underwent static load to failure. This laboratory study is done in the Civil Engineering Laboratory, UiTM Penang by using 1000KN Universal Testing Machine. The result obtain shows by replacing a certain percentage of MK 7003 into concrete have increase the concrete strength and 10% of replacement are give the best result in term of higher compression strength and higher ultimate load at failure. The result shows the different behavior of beam contain different percentage of MK 7003